A Review on Teacher Educators’ Perception towards Computer: Exploring the Impact of Computers on Teacher Educators' Attitudes and Students' Learning (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This study examined how teacher educators’ perception towards use of computer. Computers make much benefit for people and play an important role in this information age. They impact in many areas, of course, including the educational system. Because of their huge impact for our daily life, the educational function and advantage of computer gradually attract educators' attention. Students should be able to use computers as a learning tool in classrooms to promote their learning. Technology is an essential tool for learning and teaching. It can enhance students’ learning. The results revealed that the teacher educators possessed their high attitude towards computer.